Addressing STEM teacher shortages and racial disparities: The promise of AAMUTeach and HBCU educator preparation programs - Blom, Nathan Allan; Strachan, Samantha (American Journal of STEM Education, 2025)
This article explores how the AAMUTeach program at Alabama A&M University, the state’s largest HBCU, addresses STEM teacher shortages and racial disparities in education. Funded by a 2 million grant and modeled after the national UTeach framework, AAMUTeach enables undergraduates to earn both a STEM degree and a teaching certification in four years. The program builds on the university’s strong record of producing Black STEM graduates and uses strategies such as scholarships, support staff, and culturally relevant pedagogy. Despite initial challenges, its first semester enrolled 39 students—84% of whom are Black—showing early success. AAMUTeach offers a promising model for diversifying the STEM teaching workforce and improving outcomes for underrepresented students nationwide.